ANALYSIS OF EARLY POST-OPERATIONAL COMPLICATIONS IN PATIENTS UNDERGOING LAPAROSCOPIC SURGERY FOR HIATAL HERNIA - M A Burikov; O V Shoolgin; I V Skazkin; A I Kinyakin; I A Sokirenko (Клиническая практика, 2017)
In order to identify the advantages of the original modification of Nissen fundoplication techniques and identify the safest mash material for prosthetic reinforcement of hiatal closure, was made analysis of early postoperative complications in 121 patients with hiatal hernia.The formation of the non tension fundoplication reduces the level of early postoperative complications. The usage of biological prosthesis has the advantage in comparison with synthetic ones. In general, the usage of mashes significantly increases the severity of the complaints of patients after the intervention, but most of them are within 3-14 days of the postoperative period.